COMPLIANCE ANALYSIS OF VISIT TO INTEGRATED SERVICES POS FOR TODDLERS IN THE NEW NORMAL ERA IN THE WORKING AREA OF THE TANJUNGPINANG HEALTH CENTER, TANJUNGPINANG - Melly Damayanti,; Nurul Aini Suria Saputri,; Fidyah Aminin, (International Journal of Social Science, 2022)
During the COVID-19 pandemic, monthly Integrated Services Pos health service activities have been stopped. This leads to the early detection of impaired growth and development of toddlers is not optimal, the absence of additional food for toddlers, immunization and other health services. So, it brings a negative impact on the health of toddlers as the nation’s next generation. The objective of this research was to determine the factors that cause compliance to visits the Integrated Services Pos for toddlers in the Work Area of ​​the Tanjungpinang Health Center. The research design was cross sectional. The research instrument used online questionnaire using a google form. The research was conducted in November 2020 on 93 mothers of toddlers who were taken using a purposive sampling technique. Data were analyzed by logistic regression test. The results showed that there was an influence of knowledge and attitudes of mothers and the role of cadres on compliance to visits the Integrated Services Pos for toddlers with p-value <0.05 for all variables. It is expected that cadres and midwives can provide information for mothers of toddlers about the importance of Integrated Services Pos for toddlers, especially in the new normal era